UPAYA PEMERINTAH DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA GENTENGKULON KECAMATAN GENTENG KABUPATEN BANYUWANGI - Muhammad Sahlan; Moh. Anas Syamsudin (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2022)
This study aims to see how efforts promulgated by the government and the village Gentengkulon whatever exercised by government village Gentengkulon earmarked for improving the welfare of its people .This study used the qualitative descriptive. Data collection techniques used in this research was observation, interviews and documentation .The research suggests that the village administration Gentengkulon the programs appointed to carry out the elucidation and training for women in an attempt to improve the welfare of the community economy, the elucidation and training for the improvement of the community who work as potters in assesoris for industry , a business loan programs provided by the government .